The role of A-kinase anchoring proteins in cardiovascular diseases and recent advances - Zhang, Xu; Zhu, Feng; Xiao, Zhaoqiang; Wang, Hegui (Frontiers in Cell and Developmental Biology, 2025)
Cardiovascular diseases are a major global health concern, leading to high morbidity, mortality, and disability rates. Scaffold proteins, particularly A-kinase anchoring proteins (AKAPs), play a crucial role in signal transduction within the cardiovascular system. This review provides a comprehensive analysis of AKAPs’ involvement in the pathogenesis of cardiovascular diseases, emphasizing their key function in coordinating diverse signaling molecules, directing them to specific cellular microdomains, and minimizing signal interference. Disruptions in these interactions are linked to several cardiovascular disorders, such as cardiac hypertrophy, myocardial apoptosis, heart failure, arrhythmias, dysfunction in myocardial contraction and relaxation, and hypertension. Our goal was to explore the therapeutic potential of targeting the AKAP signaling pathway and offer new perspectives for the development and application of cardiovascular drugs that modulate AKAP signaling complexes.